Marshall-Smith syndrome: the expanding phenotype. Issue 10 (October 1997) - Williams, D K; Carlton, D R; Green, S H; Pearman, K; Cole, T R
Abstract : We report a child of 3 years 9 months with the Marshall-Smith syndrome (MSS), characterised by the typical facial features, developmental delay, and advanced bone age. After the diagnosis was made at 5 months of age, careful observation for respiratory complications and failure to thrive was initiated. By 3 1/2 years of age, although our patient had no life threatening respiratory complications, investigation showed significant upper airway obstruction, which has been successfully treated. Aggressive treatment for failure to thrive has also allowed her to maintain a weight on the 50th centile. The purpose of this report is to suggest that early diagnosis and aggressive management may improve the ultimate prognosis with respect to the respiratory and feeding difficulties seen in this rare syndrome.